Localisation of the Unerupted Maxillary Canine Additional Observations - Jacobs Stanley G. (Sciendo, 1994)
Occlusal radiographs are recommended for the tube shift method used to localise the unerupted maxillary canine. Several case histories are presented to explore how diagnostic occlusal films may be obtained. The initial maxillary incisor inclination determines the vertical angulation of the tube, while the mesio-distal position of the canine crown determines the horizontal angulation of the tube to the mid-sagittal piane. Increased distances aid localisation: both the distance between the impacted tooth and its reference tooth, and the distance between the positions of the tube at exposure are significant. If an orthopantomogram and an occlnsal film are to be taken as initial radiographs, the orthopantomogram should be read first to determine the position of the tube for the occlusal film. Radiographs taken prcviously niay provide iuformation on centring the tube for the occlusal film. The horizontal tube shift between Lwo occlnsal fihns is a more sensitive means of localising canines than is the vertical tnbe shift available bctween an orthopantonmogram and an occlusal film.